The Relationship Between Confidence and Conformity in a Non-routine Counting Task With Young Children: Dedicated to the Memory of Purificación Rodríguez - Lago, Ma Oliva; Escudero, Ana; Dopico, Cristina (Frontiers in Psychology, 2021)
Counting is a complex cognitive process that is paramount to arithmetical development at school. The improvement of children's counting skills depends on their understanding of the logical and conventional rules involved. While the logical rules are mandatory and related to one-to-one correspondence, stable order, and cardinal principles, conventional rules are optional and associated with social customs. This study contributes to unravel children’s conceptual understanding of counting rules. It explored, with a developmental approach, children’s performance on non-routine counting detection tasks; their confidence in their answers (metacognitive monitoring skills), and their ability to change a wrong answer by deferring to the opinion of a unanimous majority who justified or did not justify their claims. 149 children aged 5 to 8 years were randomized to one of the experimental conditions of the teachers’ testimony: with (n = 74) or without justification (n = 75). Participants judged the correctness of different types of counting procedures presented by a computerized detection task, such as: (a) pseudoerrors, that are correct counts where conventional rules are violated (e.g., counting first six footballs, followed by other six basketballs that were interspersed along the row). And (b) compensation errors, that are incorrect counts where logical rules were broken twice (e.g., skipping the third element of the row and then labeling the six element with two number words, 5 and 6). Afterwards, children rated their confidence in their detection answer with a 5-point scale. Subsequently, they listened to the teachers’ testimony and showed conformity or not. Our participants considered both compensation errors and pseudoerrors as incorrect counts in the detection task. The analysis of children’s confidence in their responses suggested that they were not sensitive to their incorrect performance. Finally, children tended to conform more often after hearing a justification of the testimony than after hearing only teachers’ testimonies. It can be concluded that children of the age range evaluated failed to recognize the optional nature of conventional counting rules and were unaware of their misconceptions. Nevertheless, the reasoned justifications of the testimony, offered by a unanimous majority, promoted considerable improvement in children’s tendency to revise those misconceptions.